MCO the real solution OR ... - Rusli, Mohammad Farhan (Astro Awani Network Sdn Bhd, 2021)
"The first movement control order (MCO) that was done in March showed that the country had placed in an effective drastic measure to curb and reduce the number of COVID-19 cases in the country. This was also taken further by imposing strategic Enhanced Movement Control Orders (EMCO) as targeted areas or hotbeds of the virus to contain it from spreading into the larger community. This proved to be a huge success as there was even 0 new cases reported."